El lenguaje jurídico claro en el Perú: avances y perspectivas - Roque Roca, Naffis Rubén (2024)
Written legal communication is difficult to understand for most Peruvians. This situation generates the loss of confidence in legal institutions and the  violation of people’s right to understand. Therefore, this study regains importance because it allows us to know the status of clear legal language in Peru and the initiatives for its implementation. From the point of view of usefulness, this research allows us to reflect on the advances of legal language in our country and the possibilities of what can be done from different governmental and private environments contribute to more fluid and understandable communication with citizens. The objective of this research is to know the state of clear legal language; identify their progress, know the projections and present suggestions for the implementation of clear language. Throughout the process, the descriptive-documentary method has been used.